Pengaruh Skeptisime Profesional Terhadap Upaya Pendeteksian Kecurangan (Case Study pada PT BPR Cianjur Jabar) - Shopia, Mia; Nugroho, Gatot Wahyu; Eriswanto, Elan (Universitas Nusantara PGRI Kediri, 2020)
This study aims to analyze the effect of independent variables on the dependent variable, namely professional skepticism and auditor independence of fraud detection efforts. PT BPR Cianjur Jabar who became respondents in this study by distributing questionnaires. The sampling technique used in this study is convenience sampling technique. The results found in this study are that professional skepticism and auditor independence influence fraud detection efforts. This was stated because this research had been tested. The test used is multiple linear regression test.